Business model canvas : Huawei Technologies Co., Ltd. / Muhammad Aiman Hakim Rohani - Hakim Rohani, Muhammad Aiman (2020)
Huawei is a Chinese multinational telecommunications equipment and services company headquartered in Guangdong, China. Founded by Ren Zhengfei in 1987, the company originally focused on manufacturing phone switches, but has expanded its operations to building telecommunications networks and manufacturing communications devices. Huawei works with some of the world’s largest telecoms operators, counting British Telecom (BT), Vodafone, Orange, and T-Mobile among its notable partners. This continued success has made the company the most valuable telecom infrastructure brand worldwide with an estimated brand value of more than 62 billion U.S. dollars.